ANALISIS PENYALURAN KREDIT KOPERASI WANITA UNIT SIMPAN PINJAM DI KABUPATEN TRENGGALEK - Sefitri Ristia Dewi; M. Faisal Abdullah; Arfida Boedirochminarni (Jurnal Ilmu Ekonomi JIE, 2018)
The objective of this study is examine the impact of grants fund, principal and compulsory savings on credit Disbursement in Women Cooperative in Trenggalek Regency. In this study, data are  collected both primary and secondary from the Trade, Cooperative, Industry, Mining and Energy Office of Trenggalek. The analysis of data used quantitative descriptive method. Based on the analysis, it can be concluded that grant fund and savings have a positive and significant effect, principal saving also has a positive and insignificant effect. It means that grant funds, principal savings, but  mandatory savings existing in the cooperative greatly affect to credit disbursement of women bsded cooperatives in Trenggalek Regency. Keywords: cooperatives, disbursement, grant funds, principal savings, mandatory savings